Pengaruh Iklim Kerja, Komunikasi Interpersonal Dan Beban Kerja Serta Kompensasi Terhadap Kepuasan Kerja Pegawai Di Puskesmas Talang Kabupaten Solok - Zulfanardi Zulfanardi; Elfindri Elfindri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2019)
The purpose of this study was to determine the extent of the influence of Work Climate, Interpersonal Communication and Workload and Compensation for Employee Job Satisfaction at Talang Health Center, Solok Regency, both simultaneously and partially and to find out the dominant variables that affect the Job Satisfaction. Talang Health Center, Solok Regency is a research location with 60 respondents. Based on the analysis of the analysis it is known that the variable work climate, interpersonal communication, workload, and compensation have a positive and significant effect on job satisfaction with the compensation variable as the variable that has the biggest effect on job satisfaction.